Ökonomische Herstellung von Feinchemikalien: Tetronsäure - Thomas Meul; Raimund Miller; Leander Tenud (CHIMIA)
Tetronic acid (1) is synthesized from ethyl 2,4-dichloroacetoacetate (11) via 3-chlorotetronic acid (9). Ring closure of 11 to 9 is achieved by pyrolysis at normal pressure. In contrast to the bromo-derivative 8, the catalytic conversion of 9 to 1 takes place in water in the absence of base. In this way the large-scale separation of 1 from salts is avoided. The described process affords a high-quality product in an overall yield of 75%.